Tentorial meningiomas with special aspect to the tentorial fold: management, surgical technique, and outcome - Hashemi, Majid; Schick, Uta; Hassler, Werner; Hefti, Martin (Acta neurochirurgica, 2010)
From a surgical perspective, tentorial fold (TF) meningiomas (TFM) are a unique entity of tumors. They involve the supra- and infratentorial space and often are in close contact to the cavernous sinus, cranial nerves, and the mesencephalon. Complete resection is challenging and can be hazardous. We present our experience with this rare tumor entity and demonstrate the surgical outcome related to a topographical classification.